LncRNA ENSMUST00000155383 is Involved in the Improvement of DPP-4 Inhibitor MK-626 on Vascular Endothelial Function by Modulating Cacna1c-Mediated Ca2+ Influx in Hypertensive Mice - Zhang, Yi; Tan, Na; Zong, Yi; Li, Li; Zhang, Yan; Liu, Jian; Wang, Xiaorui; Han, Wenwen; Liu, Limei (Frontiers in Molecular Biosciences, 2021)
Objective: This study investigated the protective effects of dipeptidyl peptidase-4 inhibitor MK-626 on vascular endothelial function by regulating lncRNAs in hypertensive vasculature. Methods: Angiotensin Ⅱ (Ang Ⅱ)-loaded osmotic pumps were implanted in mice with or without MK-626 administration. GLP-1 levels in plasma were measured by ELISA. Aortic rings were suspended in myograph for tension measurement. Microarray was performed to analyze lncRNA and mRNA expression profiles. Protein expression and phosphorylation were examined by Western blot. The differentially expressed (DE)-genes were validated by qRT-PCR. The intracellular Ca2+ concentration was detected by laser confocal system. Results: MK-626 elevated plasma GLP-1 level, increased eNOS phosphorylation, improved endothelium-dependent relaxations, and reduced systolic blood pressure in Ang Ⅱ-induced hypertensive mice. Microarray revealed the dysregulations of 723 lncRNAs and 742 mRNAs were reversed by MK-626 in hypertensive mouse aortae. qRT-PCR validation showed that 13 DE-lncRNAs and 8 dysregulated mRNAs in both hypertensive mouse aortae and mouse aortic endothelial cells (MAECs) were rescued by MK-626. Among them, 4 mRNAs (Cacna1C, Itgav, Itga8, and Npnt) were co-expressed with lncRNA ENSMUST00000155383. Cacna1C protein expression was reduced in the ECs but was elevated in smooth muscle cells from Ang Ⅱ-infused mice, which were both reversed by MK-626. Knockdown of lncRNA ENSMUST00000155383 suppressed the increased Cacna1c protein and mRNA expression, elevated Ca2+ level, and enhanced eNOS phosphorylation induced by MK-626 in the hypertensive mouse ECs. Conclusion: The dysregulations of lncRNA ENSMUST00000155383-associated genes might play crucial roles in hypertension-induced endothelial dysfunction through affecting calcium pathway. MK-626 might ameliorate endothelial dysfunction by upregulating lncRNA ENSMUST00000155383, enhancing Ca2+ concentration, and subsequently restoring eNOS activity in hypertension.